2021
DOI: 10.1007/s10461-021-03396-5
|View full text |Cite
|
Sign up to set email alerts
|

Harambee! 2.0: The Impact of HIV-Related and Intersectional Stigmas on HIV Testing Behaviors Among African Immigrant Communities in Seattle, Washington

Abstract: African immigrants are disproportionately affected by HIV compared to U.S.-born individuals, and early HIV testing is the key challenge in ending the HIV epidemic in these communities. HIV-related stigma appears to be the most significant barrier to testing for HIV among African communities in King County, WA. In this formative study, we conducted thirty key informant interviews and five focus group discussions (n = total 72 participants) with Ethiopian, Somali, and Eritrean people living with HIV, health prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…The incorporation of gender aspects is another relevant issue in training, where the concept of intersectionality (23) is relevant, considering cultural diversity and processes such as migration, which has been remarkable in recent years in Chile, together with the results of research in which the expression of social stigmas towards people due to race and ethnicity, and/or for identifying themselves as women, have become evident (24,25,26,27) .…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of gender aspects is another relevant issue in training, where the concept of intersectionality (23) is relevant, considering cultural diversity and processes such as migration, which has been remarkable in recent years in Chile, together with the results of research in which the expression of social stigmas towards people due to race and ethnicity, and/or for identifying themselves as women, have become evident (24,25,26,27) .…”
Section: Discussionmentioning
confidence: 99%
“…( Parchem and Molock, 2022 , Zhang et al, 2021 , Wise et al, 2019 ) Other studies identified that demographic characteristics (e.g., age, sex, race/ethnicity, and educational status) might be associated with the HIV testing behaviors. ( Qiao et al, 2018 ) Much of the prior literature focused on HIV testing behaviors among specific populations, such as men who have sex with men, ( Bien-Gund et al, 2022 ) transgender, ( Tordoff et al, 2022 , Pitasi et al, 2020 ) Black racial groups, ( Uzoeghelu et al, 2021 ) youth, ( Haney-Caron et al, 2021 , Phillips et al, 2020 ) or populations from a specific region in the U.S. ( Marshall et al, 2020 , Daniel et al, 2022 ) In addition to these populations, prior studies also focused on people with mental illnesses like depression, demonstrating the potential influence of depression status on HIV testing. ( Senn and Carey, 2009 , Yehia et al, 2014 ) Our study adds to existing literature by focusing on a nationally representative sample of adults with self-reported depression across all demographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…É importante entender essas disparidades para direcionar intervenções e políticas de prevenção eficazes e garantir que todas as populações afetadas tenham acesso a cuidados de saúde adequados e apoio (Daniel et al, 2022). Haja vista que a infecção pelo HIV tem uma série de repercussões funcionais e fisiológicas no corpo humano, como na diminuição das células CD4, que são cruciais para o sistema imunológico.…”
Section: Introductionunclassified